The Impact Of The Location Of Cpi Makassar On Consumer Purchase Decisions At Starbucks Sunset Quay (CPI) - Toheba, Dion; Liang, Nadia Della; Firjathi, Dwi Nur; Pratama, Ari; Tejawinata, Kathleen; Muchtar, Muchtar (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the influence of the CPI Makassar area location on consumer purchase decisions at Starbucks Sunset Quay CPI. The approach used in this research is quantitative, with data collected through questionnaires involving a number of respondents who are customers of Starbucks Sunset Quay CPI. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) software. The analysis process includes a measurement model to link indicators with the measured constructs and a structural model to test the relationships between constructs. The results of the study show that the location of the CPI Makassar area has a positive and significant influence on consumer purchase decisions. These findings indicate that the location factor plays an important role in consumers’ decisions to visit and make purchases at Starbucks Sunset Quay CPI. This research provides implications for Starbucks to continue leveraging the advantage of its location as a marketing strategy and to enhance customer comfort and experience. The limitation of this study lies in its focus on a single main variable and a quantitative approach that does not explore other potential factors influencing consumer purchase decisions. Therefore, future research is recommended to include additional variables such as service quality